Beyond the 'Gothic' : Havergal Brian and his orchestral music of the 1930s - O'Leary, Martin (Trinity College (Dublin, Ireland). Department of Music, 2004)
This thesis presents the most detailed study yet of the music of the English composer William Havergal Brian (1876-1972). It concentrates on the orchestral music written in a single decade — the 1930s — at a time when he was arguabh at the height of his powers. The music of this decade follows on form the completion of his most famous — and notorious — work, the massive Gothic Symphony- (No. 1). The works written during this decade, and in particular the two symphonies (the second and third), were crucial in establishing a forward path after the singular symphonic scale and nature of the Gothic. This manner of symphonic composition would be sustained and developed through a total of thirty two symphonies, the last written in 1968, when the composer was ninety-two. The early chapters of the thesis discuss Brian vvithin a wider musical context. Chapter one considers a selection of early orchestral works, from two points of view. They are discussed with regard to how they reflect influences on the young Brian, and also how they show early signs of compositional traits that recur much later in his career, and particularly in the three central works of the thesis.
Keywords: Music, Ph.D.; Ph.D. Trinity College Dublin